From biomarker to targeted therapy: investigating trophoblast cell-surface antigen 2 expression in triple-negative breast cancer– insights from the national cancer institute - Noura A. A. Ebrahim; Mustafa A. Hussein; Mohamed Emam Sobeih; Nancy H. Amin (BMC Cancer)
Abstract Background Triple-negative breast cancer (TNBC) is characterized by its aggressive behavior and limited treatment options, primarily due to the lack of expression of estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor 2 (HER2). TROP-2, a transmembrane glycoprotein, exhibits notable overexpression in a spectrum of highly aggressive cancers including pancreatic, gastric, and ovarian cancers. This overexpression has established TROP-2 as a key prognostic biomarker and a promising target for therapeutic intervention. Objective This research examines the correlation between TROP-2 expression and clinicopathological features in TNBC, assessing its utility as both a prognostic indicator and a candidate for targeted precision therapy. Methods Retrospective analysis of 80 TNBC patient samples from January 2016 to December 2019 at the National Cancer Institute, Cairo University, Egypt was carried out. Formalin-fixed, paraffin-embedded (FFPE) tissues were evaluated for TROP-2 expression using immunohistochemistry. Clinical and pathological data including patient demographics, tumor characteristics, treatment modalities, and survival outcomes were gathered. TROP-2 expression was correlated with clinicopathological variables and survival metrics (overall survival, OS; disease-free survival, DFS). Results A high expression of TROP-2 was observed in 78% of cases, exhibiting notable heterogeneity in intensity, proportion of positive cells, and H-score. TROP-2 expression correlated with larger tumor dimensions and advanced nodal involvement, suggesting its contribution to tumor aggressiveness. Elevated TROP-2 intensity and H-scores were significantly associated with poorer overall survival (OS; p = 0.003 and p = 0.007, respectively) and disease-free survival (DFS; p = 0.002 for both). Multivariate analysis revealed TROP-2 intensity, percentage of expression, and H-score as independent predictors of OS (p = 0.02, 0.001, and 0.012, respectively). Similarly, these variables were identified as independent prognostic indicators for DFS, with significant p-values of 0.002, 0.009, and 0.002. Conclusions Our research validates TROP-2 overexpression as an essential prognostic marker and a potential therapeutic target in TNBC. The results endorse the use of TROP-2 expression levels for patient categorization, thereby advancing the implementation of personalized treatment strategies and accelerating the progression towards precision oncology.